Strategic Assessment of the Pentahelix Model in Addressing Prostitution Issues for Sustainable Social Development - El Rizaq, Agung Dwi Bahtiar; Sarmini (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Prostitution, the exchange of sexual services for payment, is widely regarded as a significant social issue across many countries, with no clear consensus on the best approach to solve it. However, there is a lack of research on how to solve prostitution impact in society life. This study aims to analysis the Penta helix model as a strategic approach to tackling prostitution and to identify the key of social institutions that play a significant role in resolving the issue. The research used a quantitative methodology with a percentage technique and involves 60 citizens as the sample localized citizen around former Mbaben or Madusari localization. The instrument in this study is a specially designed closed-ended questionnaire to evaluate sample views toward the Penta helix model in solving prostitution strategy by binary Likert scale. The findings show that the Government Sector received the highest level of agreement, the Business Sector ranked second, the Community Sector followed the third, the Mass Media Sector had the fourth, and the last is the Academia Sector. These results indicate that each sector can contribute effectively to a multi-sectoral approach in addressing prostitution, ensuring a more comprehensive and sustainable solution to this complex social issue.